Bidirectional seismic performance of steel beam to circular tubular column connections with outer diaphragm. - Wang, Wei (Earthquake engineering & structural dynamics.)
This paper presents an experimental investigation on the seismic behavior of H-beam to circular tubular column connections stiffened by an outer ring diaphragm. An innovative three-dimensional (3D) connection subassembly testing system was first described. Specimens representative of two-dimensional (2D) interior columns, 3D interior and exterior columns in a steel building frame were then tested to failure under unidirectional or bidirectional cyclic loads. Various specimen parameters are used to evaluate their effects on connection behavior. Test results indicate significantly different failure modes for 2D and 3D weak panel connections, with panel shear buckling and local distortion of outer diaphragm occuring only for 3D connections. The weak beam connections unexceptionally exhibited final fracture at the junction between diaphragm and beam flange. In contrast with weak beam connections, weak panel connections demonstrated better seismic performance and ductility. As a result, a seismic design philosophy considering panel zone yielding before beam flexural yielding is proposed. Based on experiment observations, small diaphragm width and simplified fillet welding are found to be feasible especially for weak beam connections, improving architectural appearance and facilitating construction. Strength evaluations also suggest that current AIJ design provisions may be appropriate when applied to panel zones in 3D connections.